PENGARUH PENYADAPAN DAN KADAR PEREKAT TERHADAP SIFAT PAPAN PARTIKEL TUSAM - Rozak Memed; I M Sulastiningsih; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1988)
The  result of  a study  on  the properties   of particle  board made  from  pine  wood  is reported  in this paper.  The pine as raw material  was classified  into  three groups  i.e.  tapped,  untapped, and combination of  them. The particle  board was manufactured by using urea formaldehyde   resin with  four  levels i.e.   6%,   8%,   10%,  and 12% by weight of wood  dry  basis.The  result  reveals  that  the  average density of  particle board  made of  tapped,   untapped,   and  combination  of  them is 0.61  g/cm3,  so that  it  can be classified as medium  density  particle  board.  The properties of particle  board were affected by both  tapping  and glue proportion.   However, density  and internal bond were affected by glue proportion  but  not  by the raw material.Except for water absorption, overall properties of particle  board made  from tapped pine  appeared to have superior properties  than that from  untapped  one.